Pemanfaatan Marketplace Shopee Untuk Meningkatkan Pemasaran Produk Terhadap UMKM Pabrik Otok Mabrur Di Desa Bungbaruh Kecamatan Kadur Kabupaten Pamekasan - Sa'diyah, Halimatus; Yulianto, Ari; Joko Wardana, Moh.; Pretty Hapsari, Atieqah (Journal of Islamic Economics Studies and Practices, 2023)
The research topic in this study is the use of the marketplace marketplace to increase product marketing for the Mabrur auto factory UMKM in Bungbaruh Village, Kadur District, Pamekasan Regency. The purpose of writing this research is to introduce marketplace shopee to increase the marketing of Oto' Mabrur products. The method used in this research is that the researcher used a qualitative approach with a descriptive research type. Data collection techniques using documentation, observation and interviews. This training program aims to help owners of oto' snack production in Bungbaruh Village improve the marketing of their products through the Shopee marketplaceplatform. Through targeted interviews and outreach, business owners are provided with the in-depth understanding and skills needed to use Shopee as an effective marketing tool. It is hoped that with the continuous application of this new knowledge, sales of hawker otto' can increase significantly and their business can grow better in a wider market. The increase in marketing and exposure on the Shopee platform is expected to open up new opportunities and business growth potential for the production of oto' snacks in Bungbaruh Village.